Happily Ever After Stories - Published by Disney Press (New York Disney Press, 2004)
A collection of five stories about princesses from Disney movies, including "Cinderella," "Snow White," "Beauty and the Beast," "Sleeping Beauty," and "Aladdin."
Include Color Illustrations
Keywords: Stories